Risk of impaired nutritional status and flare occurrence in IBD outpatients. Issue 9 (September 2019) - Spooren, Corinne E.G.M.; Wintjens, Dion S.J.; de Jong, Marin J.; van der Meulen-de Jong, Andrea E.; Romberg-Camps, Mariëlle J.; Becx, Marco C.; Maljaars, Jeroen P.; van Bodegraven, Ad A.; Mahmmod, Nofel; Markus, Tineke; Hameeteman, Wim M.; Masclee, Ad A.M.; et al.
Abstract: Background: Inflammatory bowel disease (IBD) patients are at risk of an impaired nutritional status. The impact thereof on the IBD relapse risk is clinically relevant, though sparsely investigated. Aim: The aim was to explore the association between an impaired nutritional status risk and the occurrence of disease flares in IBD outpatients participating in a longitudinal telemedicine study. Methods: IBD outpatients were recruited from the myIBDcoach study cohort, with one year clinical follow-up. Through myIBDcoach, a telemedicine tool, patients reported on disease activity and risk of impaired nutritional status ( i.e. Short Nutritional Assessment Questionnaire >1 and/or BMI < 18.5 kg/m 2 ) every one to three months. Data was analysed by generalized estimating equation modelling. Results: In total, 417 patients were included. During follow-up, 49 patients (11.8%) flared after initial clinical remission and 53 patients (12.7%) showed an increased risk of impaired nutritional status. The risk of impaired nutritional status was associated with flare occurrence (OR 2.61 (95% CI 1.02–6.69)). Conclusions: The risk of an impaired nutritional status was associated with subsequent flares in IBD outpatients. This emphasizes the importance of monitoring disease activity in IBD patients at risk of impaired nutritional status.